New Paradigm in the Role of Regulatory T Cells During Pregnancy - Tsuda, Sayaka; Nakashima, Akitoshi; Shima, Tomoko; Saito, Shigeru (Frontiers in Immunology, 2019)
Semi-allogenic fetuses are not rejected by the maternal immune system because feto-maternal tolerance induced by CD4+CD25+FoxP3+ regulatory T (Treg) cells is established during pregnancy. Paternal antigen-specific Treg cells accumulate during pregnancy, and seminal plasma priming plays an important role in expanding paternal antigen-specific Treg cells in mouse models. Although paternal-antigen specific Treg cells have not been identified in humans, recent studies suggest that antigen-specific Treg cells exist and expand at the feto-maternal interface in humans. Studies have also revealed that reduction of decidual functional Treg cells occurs during miscarriage with normal fetal chromosomal content, whereas insufficient clonal expansion of decidual Treg cells is observed in preeclampsia. In this review, we will discuss the recent advances in the investigation of mechanisms underlying Treg cell-dependent maintenance of feto-maternal tolerance.